Adsorption of Fluoxetine and Venlafaxine onto the Marine Seaweed Bifurcaria bifurcata - Silva, Andreia (2019)
Marine macroalga Bifurcaria bifurcata was investigated as sorbent for two environmental emerging pollutants, the pharmaceuticals venlafaxine (VLF) and fluoxetine (FLX), from aqueous solutions, both in mono and bicomponent batch systems. The alga was characterized by means of IR spectroscopy, allowing to identify the most important groups for biosorption, carboxylic, sulfonic and hidroxile. The point of zero charge was determined, being 6.4. Adsorption of FLX follows a pseudo first order kinetics and kinetic constants are higher for FLX than for VLF. Its adsorption better represented by the pseudo second order model. For both pharmaceuticals, the equilibrium was reached within *100 min. Adsorption studies reveal that the process was more efficient at lower pH range and followed the Langmuir–Freundlich’s model for VLF and Langmuir’s model for FLX. Maximum adsorption capacities reached a level of 12 – 3 and 22 – 4 lmol/g for VLF and FLX, respectively, in the mono-component system. The difference was attributed to the presence of various functional groups of varying polarity within the adsorbates’ molecules that affected their interactions with the adsorbent surface. The Langmuir–Freundlich’s extended model was applied to the adsorption data of the bicomponent system and no changes in the maximum adsorption capacities were found (14 – 2 and 20 – 3 lmol/g for VLF and FLX, respectively), there is no evidence of competition between the adsorbates.